Prognostic factors for survival after salvage total laryngectomy following radiotherapy or chemoradiation failure: a 10‐year retrospective longitudinal study in eastern Denmark. (6th September 2016) - Wulff, N.B.; Andersen, E.; Kristensen, C.A.; Sørensen, C.H.; Charabi, B.; Homøe, P.
Abstract : Objective: The primary aims were to determine the rates of and prognostic factors for overall survival, disease‐specific survival and disease‐free survival following salvage total laryngectomy. Design: Retrospective longitudinal study. Setting: Tertiary medical centres. Participants: A total of 142 patients in eastern Denmark undergoing salvage total laryngectomy for squamous cell carcinoma of the larynx or hypopharynx. Main outcome measures: 5‐year overall survival, 5‐year disease‐specific survival, 5‐year disease‐free survival and prognostic factors for these outcomes. Results: 5‐year overall survival, disease‐specific survival and disease‐free survival were 37.7%, 54.9% and 55.3%, respectively. N classification at primary diagnosis, lymph node excision and postoperative complications within 1 year after salvage total laryngectomy were prognostic factors for shorter overall survival, disease‐specific survival and disease‐free survival. Residual tumour/recurrence was negatively associated with overall survival, close or involved resection margins with disease‐specific survival, and second primary cancer was associated with longer disease‐specific survival and disease‐free survival. Nine per cent of all patients had residual tumour and 33.8% developed a recurrence. Conclusion: Our overall survival, disease‐specific survival and disease‐free survival findings are in accordance with previous studies. With the purpose of identifying recurrent tumour, we suggest extra attention being given to patients with higher N classification and need for lymph node excision during salvage total laryngectomy along with use of frozen sections. The high number of patients with recurrence within 1 year after salvage total laryngectomy occurred although thorough and regular follow‐up visits were performed.